Determinants of Food Management Behavior on Food Waste Reduction and Household Food Security through Expenditure Efficiency and Energy Consumption - Prita Dhyani Swamilaksita; Yayuk Farida Baliwati; Drajat Martianto; Dodik Briawan (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Food Waste (FW) in urban households remains a serious issue as it contributes to economic losses, reduced dietary quality, and weakened food security. This study aims to identify the dominant factors influencing food management behavior, FW generation, and their implications for household food security in urban settings. A cross-sectional design was applied with urban households as the study population, and samples were selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) within the framework of the Theory of Planned Behavior (TPB) and Nudge Theory. The results indicate that attitude (β = 0.42; p < 0.01), subjective norm (β = 0.31; p < 0.05), and perceived behavioral control (β = 0.36; p < 0.01) significantly influence intention toward food management. Furthermore, intention strongly predicts actual food management behavior (β = 0.55; p < 0.001), which subsequently reduces FW (β = –0.47; p < 0.001). Reduced FW positively affects both food expenditure efficiency (β = 0.39; p < 0.01) and energy intake adequacy (β = 0.34; p < 0.05), two critical indicators of urban household food security. Behavioral factors play a crucial role in reducing FW and strengthening food security in urban households. Therefore, behavior-based interventions using TPB and Nudge Theory are recommended to be integrated into food education programs, household assistance, and urban food security policies to ensure effectiveness and sustainability.